2022
DOI: 10.7150/thno.64233
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the anti-apoptotic Bcl-2 family proteins: machine learning virtual screening and biological evaluation of new small molecules

Abstract: Bcl-2 family anti-apoptotic proteins are overexpressed in several hematological and solid tumors, and contribute to tumor formation, progression, and resistance to therapy. They represent a promising therapeutic avenue to explore for cancer treatment. Venetoclax, a Bcl-2 inhibitor is currently used for hematological malignancies or is undergoing clinical trials for either hematological or solid tumors. Despite these progresses, ongoing efforts are focusing on the identification and development of new molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…Moreover, docking experiments indicated that IS21 is able to displace more effectively BH3 helix from Bcl-2 and Bcl-xL and with lower potency from Mcl-1. All these data con rmed the docking analysis and are in good agreement with the Surphace Plasmon Resonance experimental data previously published [41], indicating that the main targets of IS21 are Bcl-2 and Bcl-xL. Also, Mcl-1, although endowed with less a nity towards IS21 than Bcl-xL and Bcl-2, may represent an important player dictating the IS21 response in our biological settings.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Moreover, docking experiments indicated that IS21 is able to displace more effectively BH3 helix from Bcl-2 and Bcl-xL and with lower potency from Mcl-1. All these data con rmed the docking analysis and are in good agreement with the Surphace Plasmon Resonance experimental data previously published [41], indicating that the main targets of IS21 are Bcl-2 and Bcl-xL. Also, Mcl-1, although endowed with less a nity towards IS21 than Bcl-xL and Bcl-2, may represent an important player dictating the IS21 response in our biological settings.…”
Section: Discussionsupporting
confidence: 89%
“…IS21 and ABT-199 sensitize BRAF mutant melanoma cells to MAPKi in vivo IS21 and ABT-199, administered as single agents, were previously reported to reduce in vivo tumor growth of melanoma models [41]. To evaluate their effect in combinatorial regimes and to validate our results in vivo, mice carrying A375luc tumors were treated with double (dabrafenib + trametinib), or triple (dabrafenib + trametinib + IS21 or dabrafenib + trametinib + ABT-199) combinations (Fig.…”
Section: Bh3 Mimetics Synergistically Potentiate the Effect Of Parp I...mentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer cells often over-express different proteins that have a major contribution in resisting the cascade of apoptosis. Multiple mechanisms induced by cancer cells rescue them from programmed cell death, especially through the over-expression of the anti-apoptotic molecules [ 7 ]. In fact, the majority of apoptosis signaling research is dependent on B-cell lymphoma 2 homology 3 (BH3) proteins [ 8 ].…”
Section: Introductionmentioning
confidence: 99%